1993
DOI: 10.1007/bf00211040
|View full text |Cite
|
Sign up to set email alerts
|

Interval mapping of quantitative trait loci for reproductive, morphological, and seed traits of soybean (Glycine max L.)

Abstract: Quantitative trait loci (QTL) were mapped in segregating progeny from a cross between two soybean (Glycine max (L.) Merr.) cultivars: 'Minsoy' (PI 27.890) and 'Noir 1' (PI 290.136). The 15 traits analyzed included reproductive, morphological, and seed traits, seed yield and carbon isotope discrimination ratios ((13)C/(12)C). Genetic variation was detected for all of the traits, and transgressive segregation was a common phenomenon. One hundred and thirty-two linked genetic markers and 24 additional unlinked ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
147
2
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(172 citation statements)
references
References 21 publications
17
147
2
6
Order By: Relevance
“…Therefore, it can be concluded that the evaluated traits are under environment effects, as well as that the present population can be used in studies aimed at evaluating heritability of such traits. Mansur et al (1993) that the LGs C1, C2 and D1 have loci associated with the traits leaf area and maturity of the soybean. The identification of a QTL associated with W ST in the LG L confirms the observation that in this LG there is a QTL associated with WST (Santos et al, 2006) and plant height of G. max (Lee et al, 1996).…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, it can be concluded that the evaluated traits are under environment effects, as well as that the present population can be used in studies aimed at evaluating heritability of such traits. Mansur et al (1993) that the LGs C1, C2 and D1 have loci associated with the traits leaf area and maturity of the soybean. The identification of a QTL associated with W ST in the LG L confirms the observation that in this LG there is a QTL associated with WST (Santos et al, 2006) and plant height of G. max (Lee et al, 1996).…”
Section: Discussionmentioning
confidence: 96%
“…None of the classical major genes controlling flowering and maturing times that have been mapped so far is located in LG O. Many QTL influencing the flowering and maturing times have been allocated to various LGs (Keim et al 1990;Mansur et al 1993;Lee et al 1996;Orf et al 1999;Tasma et al 2001;Yamanaka et al 2001;Chapman et al 2003;Watanabe et al 2004;Zhang et al 2004;Funatsuki et al 2005;Liu et al 2007). However, only a maturitycontrolling QTL has been located in LG O (Zhang et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Diers et al (1992) used the same interspecific soybean population to identify several molecular marker loci that were significantly associated with QTLs for seed protein and oil. Other workers utilized molecular markers to identify several genomic regions significantly associated with seed protein, oil, seed weight and sucrose content in different intraspecific soybean populations (Mansure et al, 1993;Lee et al, 1996;Mian et al, 1996;Maughan et al, 1996;Brummer et al, 1997). The objective of this study was to use SSR markers to identify quantitative trait loci associated with seed coat permeability and electrolyte leaching in an intraspecific F 2 soybean population.…”
mentioning
confidence: 99%